Analysis of Indonesian Malay Cultural Assembly Participation in the 2018 Election of Regional Heads of Batubara Regency - Fahri Iswahyudi; Subhilhar; Heri Kusmanto (PERSPEKTIF, 2023)
This study aims to analyze the participation of the Indonesian Malay cultural adat assembly in the regional head elections in Batubara district in 2018. The Malay Cultural Customary Council is an organization or institution that aims to defend, promote and preserve Malay customs and culture. As part of the people who vote in the Pilkada (Regional Head Election) in Batu Bara Regency, of course, their participation is expected. However, the extent of participation in the regional head election in Batubara district in 2018. This research uses a qualitative research type method with a descriptive method, namely collecting descriptive data for further analysis from the case study. Data collection was carried out by means of interviews, document analysis, observation and literature study. The results of the study show that the factors that influence the participation of the Indonesian Malay Cultural Council Organization in Batu Bara Regency include: First, the political awareness of the people regarding their rights and obligations in the 2018 Pilkada is only limited to understanding, without being accompanied by controlling the course of the 2018 Pilkada and exercising their right to vote. Second, the low level of public trust in the government and candidates, which includes a track record and vision and mission, greatly affects the people not to exercise their right to vote. Third, the social status and economic status of the upper middle and lower middle class do not make voting a priority due to the focus on the work of the majority of fishermen and entrepreneurs.